Síndrome de Down : correlações entre habilidades manuais, composição corporal e lateralidade funcional - Souza, Aline Bernardes de (2015)
The objective of this study was to investigate the correlation between the variables of body composition, hand ability and functional laterality in people with Down syndrome (DS) and compare them to a control group (CG). It had the participation of 30 people with DS and 30 individuals without developmental changes, aged 11-14 years old, of both sexes. To this end, the following measurements were taken: hand grip strength (HGS) by Jamar® dynamometer; body composition and nutritional status through the body mass index (BMI), body fat percentage (BFT), arm muscle circumference (AMC) and forearm circumference (FC); manual functional performance verified by Box and Blocks Test (BBT) and the seven tasks protocol by Jebsen-Taylor. The lateral domain (LD) was evaluated by Negrine protocol and preference manual (PM) analyzed by Van Strien protocol. To analyze the results we used the Wilcoxon test to compare the means and the Spearman correlation test. The results showed higher percentage of individuals left-handed in group with DS, GDS, (33.3%) than in the CG (13.3%), and beside biggest preference manual to right as CG as GDS. The CG showed better performance than the GDS in all tasks, observing better results with the preferred hand for CG. The HGS correlated with FC and with some Jebsen-Taylor tasks in both groups, but there was no statistically significant correlation with the BBT as GDS as CG. The correlation between BFT and FC was statistically significant for the CG and the GDS and between BFT and three of the seven assessed manual tasks. There was not statistically significant difference between the BFT measured in hemi bodies for both groups. This study provides a differential use of the Jebsen-Taylor protocol in people with DS, who was sensitive to it than verification of the correlation of body composition with motor coordination in individuals with abnormal development. The differences in the development and performance of the person with DS deserve further investigation so that the knowledge of its peculiarities is amplify thus seeking new forms of assessment and intervention that may improve its performance, minimizing the delay to be expected.